Laparoscopic radical antegrade modular pancreatosplenectomy vesus laparoscopic distal pancreatosplenectomy for left-sided pancreatic cancer: a systematic review and meta-analysis - Jiang, Xutao; Zhu, Yu; Li, Jianwei; Li, Wei; Zheng, Weizong; Xu, Caiming; Zhang, Guixin (Frontiers in Oncology, 2025)
ObjectiveWe aimed to compare the perioperative outcomes and postoperative complications of laparoscopic radical antegrade modular pancreatosplenectomy (L-RAMPS) versus laparoscopic distal pancreatosplenectomy (L-DPS) for left-sided pancreatic cancer through a meta-analysis.MethodsA systematic review and meta-analysis, conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, were performed. Literature searches were conducted in PubMed, Web of Science, Cochrane Library, and Embase for studies published from their inception up to June 14th, 2024.ResultsA total of three retrospective studies involving 242 patients were included in this meta-analysis, with 116 patients in the L-RAMPS group and 126 in the L-DPS group. The meta-analysis results indicated that L-RAMPS was associated with the retrieval of more lymph nodes (MD: 3.06; 95% CI: 2.51 to 3.62, p < 0.00001) and longer operative time (MD: 20.05; 95% CI: 13.97 to 26.12, p < 0.00001) compared to L-DPS for left-sided pancreatic cancer patients. However, no significant differences were observed between the two groups in terms of R0 resection margins, the incidence of pancreatic fistula (Grade B and C), postpancreatectomy hemorrhage, or postoperative complications (Clavien-Dindo Grades II and III).ConclusionsIn patients with left-sided pancreatic cancer, L-RAMPS resulted in the retrieval of more lymph nodes, a longer operative time, and a similar incidence of postoperative complications compared to L-DPS. Larger sample sizes, extended follow-up periods, and well-conducted randomized controlled trials are needed to further validate these findingsSystematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=558977, identifier CRD42024558977.